Regional differences in health care of patients with inflammatory bowel disease in Germany - Ansgar Lange; Anne Prenzler; Frank Oliver Bachmann; Roland Linder; Sarah Neubauer; Jan Zeidler; Michael P. Manns; Johann-Matthias Graf von der Schulenburg (Health Economics Review, 2015)
Background: The regional availability of specialized physicians is an important aspect in healthcare of patients with IBD. The association between physician density and healthcare is not yet clear. Most studies did not consider district type, which reflects population density. Our research question was, "Do specialist density and district type influence the healthcare of IBD patients in Germany?" Methods: We combined a claims dataset from a German health insurance fund with population and physician data. Four main aspects were investigated: regular specialist visits, drug therapies, surveillance colonoscopy, and IBD-related hospitalizations. Various regression analyses were performed. Results: The study cohort was comprised of 21,771 individuals, including 9282 patients with Crohn disease and 12,489 patients with ulcerative colitis. Patients who were living in districts with higher specialist densities were more likely to attend specialist visits on a regular basis. No difference in the frequencies of TNF-alpha inhibitor therapies was found. However, individuals from urban areas were more likely to receive a permanent immunosuppressive therapy with continuous specialist support. Conclusions: The results revealed that some aspects had positive effects on the probability of implementing healthcare in accordance with pathways and guidelines. No clear evidence of a general healthcare undersupply in rural areas was found.
Keywords: I10; I11; I18; 330; Inflammatory bowel disease; Quality; Regional differences; Guidelines; Crohn; Ulcerative colitis